Insan Qur ani abad modern Abbas Mahmud Al-Aqqod ; penerjemah, Ainur Roziq AR dan Fateh Rahmat ; penyunting, Umar Sufyan - AL-AQQAD, Abbas Mahmud; Roziq Ar, Ainur; Rahmat, Fateh (Titian Ilahi Press, 1995)
90 hlm 20 cm